Flexible self-repairing touch screen based on perovskite-graphene heterojunction

By optimizing the perovskite-graphene heterojunction interface and introducing efficient self-repair materials, combined with intelligent energy management algorithms, the mechanical durability and energy management adaptability of flexible touch screens are solved, significantly improving the environmental adaptability and service life of the equipment.

CN119916973AActive Publication Date: 2025-05-02XIN XIANG DIAN GANG KE JI YOU XIAN GONG SI
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510417241.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-03
Publication Date
2025-05-02
Estimated Expiration
2045-04-03

AI Technical Summary

Technical Problem

Existing flexible touch screens are susceptible to damage in flexible applications, insufficient mechanical durability, low self-repair efficiency, poor energy management adaptability, resulting in insufficient environmental adaptability and service life of the equipment.

Method used

By optimizing the perovskite-graphene heterojunction interface structure, introducing efficient self-repair materials and developing intelligent energy management algorithms, we can improve photoelectric conversion efficiency, mechanical durability and environmental adaptability, and achieve stable and reliable energy supply.

Benefits of technology

It significantly improves the photoelectric conversion efficiency, mechanical durability and environmental adaptability, achieves the conductivity recovery rate ≥90%, improves mechanical durability, and is more intelligent in energy management, with a touch response delay of ≤10 ms and an error touch rate ≤2%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119916973A_ABST
    Figure CN119916973A_ABST
Patent Text Reader

Abstract

The invention discloses a flexible self-repairing touch screen based on a perovskite-graphene heterojunction and a mobile terminal device. Comprising the following components stacked in sequence: (a) a flexible transparent substrate, (b) a perovskite photovoltaic layer arranged on the substrate, (c) a graphene conductive layer covering the perovskite photovoltaic layer, and (d) a self-repairing functional layer embedded in the graphene conductive layer, and further comprises an energy management module electrically connected with the graphene conductive layer, comprising an energy storage unit composed of a miniature supercapacitor and a lithium ion battery which are connected in parallel, and a power distribution chip integrated with an adaptive algorithm. The graphene conductive layer and the perovskite photovoltaic layer form continuous defect-free heterojunction interface optimization, and the photoelectric conversion efficiency reaches 25.6% (AM 1.5 G illumination) and is improved by 40% compared with a traditional ITO electrode. Meanwhile, the system also has more prominent self-repairing capability and more intelligent energy supply management.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of flexible electronic devices, and specifically to a flexible self-repairing touch screen based on a perovskite-graphene heterojunction. The touch screen integrates a perovskite photovoltaic layer, a graphene conductive layer, a dynamic self-repairing functional layer and an intelligent energy management module. The touch screen is suitable for flexible display scenarios such as wearable devices and foldable screen mobile phones, and can significantly improve the environmental adaptability and service life of the device through self-power supply and self-repairing mechanisms. Background Art

[0002] As an important display electronic device, touch screens are widely used in industrial and consumer electronic products, especially in mobile terminal devices such as smartphones, pads, wearable devices, etc. However, traditional touch screens are easily damaged in flexible applications, resulting in display failure and difficult repair, which greatly limits the reliability of the device and user experience. In addition, traditional touch screens have high energy consumption and cannot meet the battery life requirements of portable devices. In order to solve the battery life problem when charging is inconvenient, Infinix, a brand under Shenzhen Transsion Holdings Co., Ltd., and BOE Technology Group Co., Ltd. jointly launched the first perovskite photovoltaic charging mobile phone, which has a perovskite photovoltaic layer on the back of the phone, using its high energy conversion efficiency to achieve self-powered function, effectively extending the battery life of the device. However, in terms of charging of touch screens, there is still a blank. For this reason, people have never stopped using perovskites in consumer electronics.

[0003] 1. Application of Perovskite-Graphene Heterojunction Perovskite materials are widely used in photovoltaic devices due to their high light absorption coefficient and adjustable band gap characteristics. Graphene is often combined with perovskite as a transparent electrode material due to its high conductivity and flexibility. However, in the prior art, the interface between perovskite and graphene often has defects due to lattice mismatch, which affects the carrier transfer efficiency.

[0004] 2. Limitations of self-healing materials Existing self-healing materials for flexible electronic devices are mostly designed with microcapsules or dynamic covalent bonds. For example, polyurethane microcapsules encapsulating conductive polymer repair agents can respond to mechanical damage, but the conductivity recovery rate after repair is usually less than 80%. In addition, the glass transition temperature (Tg) of the dynamic covalent bond network is ) has a narrow range (40-60℃), which makes it difficult to adapt to repair needs in high or low temperature environments.

[0005] 3. Energy management challenges of flexible touch screens Traditional flexible touch screens rely on external power supplies, which limits their energy density and battery life. Although the perovskite photovoltaic layer can power the device, its output power is significantly affected by ambient light and mechanical deformation. Existing energy management algorithms are mostly fixed-mode control and cannot adjust the power supply strategy in real time, which can easily lead to overload or insufficient power supply in strong light or high-load scenarios.

[0006] Summary of technical issues: 1. Interface defects and insufficient mechanical durability: Interface defects between perovskite and graphene heterojunctions lead to attenuation of photoelectric conversion efficiency, and flexible substrates are prone to breakage during repeated bending.

[0007] 2. Low self-healing efficiency: Existing self-healing materials have low conductivity recovery rates and limited operating temperature ranges.

[0008] 3. Poor adaptability of energy management: Traditional algorithms cannot dynamically respond to changes in multiple parameters such as light, pressure, and equipment deformation, resulting in unstable energy supply. Summary of the invention

[0009] In response to the above technical problems, the purpose of the present invention is to provide a new type of flexible touch screen, which significantly improves the photoelectric conversion efficiency, mechanical durability and environmental adaptability by optimizing the perovskite-graphene interface structure, introducing high-efficiency self-healing materials and developing intelligent energy management algorithms, so as to achieve stable and reliable energy supply.

[0010] In order to achieve the above object, the present invention adopts the following technical solutions: A flexible self-repairing touch screen based on a perovskite-graphene heterojunction comprises the following sequentially stacked components: (a) Flexible transparent substrate made of polyimide (PI) or polyethylene terephthalate (PET), with a thickness of 10-50 μm and a plasma-treated surface; (b) a perovskite photovoltaic layer disposed on the substrate, wherein the material of the perovskite photovoltaic layer is formamidinium lead iodide perovskite ( ) or methylamine lead bromide perovskite ( ), with a thickness of 200-500 nm, and the surface is modified with graphene quantum dots to improve light absorption efficiency; (c) a graphene conductive layer covering the perovskite photovoltaic layer, which is directly grown by chemical vapor deposition (CVD) and has a square resistance of ≤50 Ω / sq and a transmittance of ≥90%, and forms a heterojunction structure with the perovskite layer; (d) a self-healing functional layer embedded in the graphene conductive layer, which is a thermoreversible polymer network containing dynamic covalent bonds or a conductive polymer repair agent encapsulated in microcapsules, wherein the dynamic covalent bonds are Diels-Alder bonds, the glass transition temperature of the thermoreversible polymer network is 60-80°C, and the microcapsule rupture threshold is 0.5-2.0 MPa; (e) An energy management module electrically connected to the graphene conductive layer, comprising an energy storage unit composed of a micro supercapacitor and a lithium-ion battery connected in parallel, and a power distribution chip integrating an adaptive algorithm, wherein the algorithm calculates the real-time power supply of the touch electrode by the following formula: in: : Real-time power supply of touch electrode, unit ; L: illuminance value collected by the ambient light sensor, ; F: Touch pressure sensor feedback value, ; : Operation mode reference power, defined as follows: , : Dynamic weight coefficient, satisfying , and updated every 30 seconds according to the following formula: α: power adjustment factor, value range [0.8,1.2].

[0011] In one embodiment of the present invention, in order to improve the conductivity and interface stability, the graphene conductive layer is a double-layer AB stacked structure of a few-layer graphene film with an interlayer spacing of 0.34±0.02 nm, and the CVD method uses a methane / hydrogen mixed gas with a methane volume concentration of 5-15% and a growth temperature of 1000-1050°C. Experiments have shown that the interlayer sliding mechanism of the double-layer structure can disperse stress, and in a 100,000 bending test with a curvature radius of 5 mm, the square resistance increase is ≤8% (conventional single-layer structure ≥30%).

[0012] Furthermore, in the conductive polymer repair agent wrapped in the microcapsule, the mass ratio of polypyrrole to polyaniline is 3:1 to 1:1, the microcapsule wall thickness is 10-15% of the core material diameter, and the spatial distribution density of the microcapsule in the graphene conductive layer is In addition, the repair agent can be quickly released after the microcapsule is ruptured, forming a conductive network with the graphene layer, restoring the conductivity to more than 90% of the initial value, significantly extending the service life of the device.

[0013] Furthermore, the plasma treatment adopts a radio frequency glow discharge mode with a power density of The oxygen content of the treated substrate surface increases by 8-12 at%, and the interface binding energy with the perovskite layer is ≥ This treatment not only improves the interfacial adhesion, but also optimizes the charge transfer efficiency, allowing the device to maintain stable performance in high temperature and high humidity environments, effectively reducing the failure rate and extending the service life.

[0014] In a specific embodiment of the present invention, the weight coefficient update function further includes a resistance compensation term: in, is the initial square resistance of the graphene conductive layer, It is used to monitor square resistance in real time, in Ω / sq. By introducing resistance compensation, the system can adjust the power supply strategy in real time to ensure that the touch electrodes maintain efficient response in different environments. Experiments show that this improvement increases touch sensitivity by 20% and reduces the failure rate by 15% under extreme temperature and humidity conditions, further improving the reliability of the device and user experience.

[0015] In order to solve the problem of insufficient energy supply or circuit overload caused by instantaneous overload, which may cause interface damage, when Δω>0.8 is detected and lasts for more than 10 seconds, the emergency energy supply protocol is activated: Among them, τ=30 s is the time constant; is the real-time output power of the perovskite layer, in units .

[0016] In order to improve the conductivity recovery rate and temperature adaptability, the cross-linking density of the dynamic covalent bonds in the thermoreversible polymer network is to , and the repair efficiency satisfies: in, is the conductivity of the graphene conductive layer after self-healing treatment, is the conductivity in the original undamaged state, in S / m; is the glass transition temperature of the thermoreversible polymer network, T is the applied external heating temperature, in °C.

[0017] The present invention also provides a mobile terminal device, comprising the above-mentioned flexible self-repairing touch screen, and the energy management module is integrated with the terminal battery system through a reversible plug interface.

[0018] Furthermore, in order to solve the problems of communication delay and low power management of existing communication equipment, the communication interface between the energy management module and the terminal motherboard adopts Protocol, data transmission rate ≥ 400 kbps, and has the following collaborative control logic: in: : The state of charge of the terminal battery, ranging from 0-100%; : The safe output power of the perovskite photovoltaic layer is calculated as follows: is the real-time output power of the perovskite layer, in units .

[0019] Furthermore, the device housing is provided with a deformation sensor array linked to the self-healing functional layer, with a sensor spacing of ≤500 μm. When a bend with a curvature radius R<5 mm is detected, the following compensation mechanism is triggered: in, , is the change in curvature radius, unit: mm; is the radius of curvature of the device in the initial planar state (defined as ). By introducing the deformation sensor array and dynamic compensation mechanism, the device can still maintain stable touch performance under complex deformation, effectively extending its service life. Experimental verification shows that this mechanism increases the bending tolerance by 30%, significantly enhancing the durability of the device and user satisfaction.

[0020] Due to the adoption of the above scheme, the beneficial effects of the present invention are as follows: 1. Through the optimization of the continuous defect-free heterojunction interface formed by the graphene conductive layer and the perovskite photovoltaic layer, the photoelectric conversion efficiency reaches 25.6% (AM 1.5G light), which is 40% higher than the traditional ITO electrode; the surface-modified graphene quantum dots extend the light absorption range to 300-800 nm, and the external quantum efficiency (EQE) peak reaches 92%.

[0021] 2. Outstanding self-repairing ability. The dynamic covalent bond network (Tg=60-80℃) or microcapsule repair agent can repair cracks with a depth of ≤50 μm within 5 minutes, with a conductivity recovery rate of ≥90% and interface resistance restored to within 95% of the initial value. The repair temperature range is also wider.

[0022] 3. Energy management is more intelligent, with adaptive algorithms based on ambient light (L), touch pressure (F) and device deformation ( ) Adjust the power supply in real time, the touch response delay is ≤10 ms, and the false touch rate is ≤2%.

[0023] In addition, the device's mechanical durability, adaptability to extreme environments, and user experience have been significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a schematic diagram of the structural decomposition of the present invention; In the figure, 1. Flexible transparent substrate; 2. Perovskite photovoltaic layer; 3. Graphene conductive layer; 4. Self-healing functional layer. DETAILED DESCRIPTION

[0025] The technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0026] Example 1 like Figure 1 As shown, a flexible self-repairing touch screen based on a perovskite-graphene heterojunction includes a flexible transparent substrate 1, a perovskite optically superior layer 2, a graphene conductive layer 3 and a self-repairing functional layer 4 stacked in the following order, wherein the perovskite optically superior layer 2 is disposed on the flexible transparent substrate 1 and the material is formamidinium lead iodide perovskite ( ), with a thickness of 300nm, and the surface of the perovskite photo-optimized layer 2 is decorated with graphene quantum dots with a particle size of 10nm to improve the light absorption efficiency. The graphene conductive layer 3 is covered on the perovskite photovoltaic layer 2. The graphene conductive layer 3 is directly grown by double-layer AB by chemical vapor deposition (CVD) method, with a square resistance of ≤50 Ω / sq, a transmittance of ≥90%, and forms a heterojunction structure with the perovskite layer. The self-healing functional layer 4 is embedded in the graphene conductive layer 3. The self-healing functional layer is a microcapsule repair agent (polypyrrole: polyaniline = 2:1, wall thickness accounts for 12%), with a rupture threshold of 1.5 MPa and a distribution density of (SEM statistics).

[0027] The energy management module is electrically connected to the graphene conductive layer 3. The energy management module includes an energy storage unit composed of a micro supercapacitor and a lithium-ion battery connected in parallel, and a power distribution chip integrating an adaptive algorithm. The adaptive algorithm calculates the real-time power supply of the touch electrode through the following formula: in, Real-time power supply for touch electrodes, unit ; L is the illumination value collected by the ambient light sensor, ; F is the feedback value of the touch pressure sensor, ; is the operating mode reference power, defined as follows: , is the dynamic weight coefficient, satisfying , and updated every 30 seconds according to the following formula: α is the power adjustment factor, with a value range of [0.8,1.2]. The weight coefficient update function includes the resistance compensation term: in, is the initial square resistance of the graphene conductive layer, unit: Ω / sq; To monitor the square resistance in real time, the unit is Ω / sq; when it is detected If the condition lasts for more than 10 seconds, the emergency energy supply protocol will be activated: Among them, τ=30 s is the time constant; is the real-time output power of the perovskite layer, in units .

[0028] The present invention is described in more detail below in combination with different materials and preparation methods.

[0029] 1. Preparation and performance testing of flexible self-healing touch screen based on perovskite-graphene heterojunction: 1. Materials and structure preparation Substrate processing: A 50 μm thick polyimide (PI) film was treated with oxygen plasma (power density , processing time 90 seconds), the surface roughness was reduced from the initial 25 nm to 8 nm, and the interface bonding energy was reduced from Upgrade to (AFM test).

[0030] Perovskite photovoltaic layer: Spin coating deposition layer (300 nm thick), surface modified with graphene quantum dots with a particle size of 10 nm, and the light absorption efficiency was increased by 28% (UV-Vis test, 400-800 nm band).

[0031] Graphene conductive layer: Double-layer AB stacked graphene was grown by CVD method (methane concentration 10%, temperature 1020℃), with a square resistance of 40 Ω / sq and a transmittance of 92% (tested by four-probe method and spectrophotometer).

[0032] Self-healing functional layer: Microcapsule repair agent (polypyrrole: polyaniline = 2:1, wall thickness accounts for 12%), rupture threshold 1.5 MPa, distribution density (SEM statistics).

[0033] The performance test and data comparison are shown in Table 1.

[0034] Table 1 It can be seen from Table 1 that compared with the traditional ITO-based touch screen, the photoelectric conversion efficiency of the present invention is greatly improved, the resistance increase is small after being bent 100,000 times, and the performance is far better than the traditional ITO-based touch screen.

[0035] 2. Dynamic energy supply verification of adaptive algorithm: 1. Experimental Setup Test scene: simulated strong light ( ), high pressure (F=3.5 N) and bending (R=5 mm) combined working conditions.

[0036] Algorithm parameters: , , α=1.1, update period 30 seconds.

[0037] 2. The data records are shown in Table 2.

[0038] Table 2 3. Comparative Analysis Traditional fixed algorithm (no compensation), overload occurred 11 times within 90 seconds, and the overload incidence rate in the same scenario was 12.3%; The adaptive algorithm of the present invention has an overload occurrence rate of 0% and increases the photovoltaic energy utilization rate from 65% to 88%.

[0039] 3. Self-healing test in extreme environment 1. Test conditions Low temperature repair: -20℃ environment, apply 1.0MPa pressure to simulate cracks; High temperature repair: 100℃ environment, repair time record.

[0040] 2. The results are shown in Table 3. Table 3 4. Durability test of reversible plug interface 1. Experimental Methods Plug and unplug life test: 100,000 plug and unplug cycles, frequency is 5 times / minute; Deformation test: bend with a curvature radius of 5mm and record the change in contact resistance.

[0041] 2. Data records are shown in Table 4 Table 4 5. Low-battery endurance test of mobile terminals 1. Test scenario : Continuous touch operation (gaming mode, 120 Hz sampling rate); Photovoltaic input: , simulating a cloudy environment.

[0042] 2. Test results The present invention: the battery life is 2.8 hours, and the touch function is normal; Traditional solution: battery life is 2.0 hours, and touch function is reduced by 50%.

[0043] 6. Low power collaborative control and Communication test 1. Experimental Setup Test equipment: A foldable screen mobile phone equipped with the touch screen of the present invention, with the initial SOC value set to 25%, and the game mode is continuously run until the SOC=15%.

[0044] Communication Protocol: The interface rate is 400kbps; the comparison group uses the SPI protocol with a rate of 100kbps.

[0045] Control logic trigger conditions: 2. Data records and comparisons are shown in Table 5.

[0046] Table 5 3. Comparison results Improved low-battery life: By dynamically adjusting the power supply weight (0.7:0.3), the touch function life is extended by 40%; High-speed communication advantages: The protocol reduces data transmission delay to 1 / 4 of SPI and the bit error rate drops by 25 times; Safe Power Management: The dynamic limiting algorithm prevents circuit overload and no overload events were measured.

[0047] 7. Deformation sensor and compensation mechanism test 1. Experimental Setup Sensor array: 500 μm pitch MEMS piezoresistive sensors covering the device housing; Bending test: curvature radius R = 5 mm (critical value) and R = 3 mm (extreme value), continuous bending 100,000 times; Compensation algorithm: 2. Data records and comparisons are shown in Table 6.

[0048] Table 6 3. Comparison results Real-time deformation compensation: For every 1 mm increase, α increases by 2% (e.g. α+10% when R=5 mm), and power fluctuation is suppressed to ±3%; Extreme bending protection: When R=3 mm, the microcapsule rupture rate is reduced by 23%, and the conductivity recovery rate after repair is still ≥88%; High-precision sensing: sensor error ≤ 0.1 mm, far better than traditional solutions (±1.0 mm).

[0049] Example 2: Preparation and repair performance testing of dynamic covalent bond thermoreversible polymer networks 1. Material preparation and testing methods 1.1 Preparation of thermoreversible polymer networks raw material: Monomer: furanyl acrylate (FA) and maleimide (MI), molar ratio 1:1; Cross-linker: four-arm polyethylene glycol (PEG-4MA, molecular weight 2000 Da); Dynamic covalent bond: Diels-Alder bond (DA bond).

[0050] Synthesis steps: (a) FA and MI were prepolymerized at 60 °C for 30 min to form a linear prepolymer; (b) PEG-4MA (10% of the total mass) was added and cross-linked at 80 °C for 2 h to form a three-dimensional network; (c) The crosslink density was determined by the swelling method: .

[0051] 1.2 Performance Testing Repair temperature range: -20℃ to 100℃; Conductivity test: Four-probe method to measure the conductivity before and after repair ( ); Mechanical testing: Universal testing machine measured the tensile strength after repair (ASTM D638).

[0052] 2. Experimental results and data comparison 2.1 Repair efficiency and temperature adaptability are shown in Table 7 Table 7 2.2 Mechanical properties comparison is shown in Table 8 Table 8 3. Comparison results Compared with the traditional solution, the present invention has the following advantages: 3.1 Wide temperature range repair advantage, effective within -20℃ to 100℃, covering extreme environment requirements; 3.2 High conductivity recovery rate: ≥90% at room temperature, ≥88% after 10 cycles; 3.3 Low bending modulus: 1.2 GPa (much lower than the comparative example 2.5 GPa), adapting to the deformation requirements of flexible devices; 3.4 Precise control of cross-linking density: , balancing repair speed and mechanical strength.

[0053] Example 3: Effect of the change in thickness of the perovskite photovoltaic layer on the present invention According to the method and conditions of Example 1, perovskite photovoltaic layers with thicknesses of 100 nm, 200 nm, 300 nm, 400 nm, 500 nm and 600 nm were prepared respectively, and their electro-optical properties were tested. The test data comparison is shown in Table 9: Table 9 Comparison results: When the thickness of the perovskite photovoltaic layer is 200-500 nm, the light absorption efficiency is ≥82%, and the interface binding energy is ≥ , the resistance fluctuation after bending is small; when the thickness is too thin (such as 100 nm) or too thick (such as 600 nm), the light absorption efficiency is less than 75%, and the interface binding energy is less than , the resistance fluctuates greatly after bending.

[0054] Example 4: Effect of changes in microcapsule rupture threshold on the present invention Embodiments of microcapsule self-healing functional layers with rupture thresholds of 0.5 MPa (8% wall thickness), 1.0 MPa (10% wall thickness), 1.5 MPa (12% wall thickness) and 2.0 MPa (15% wall thickness) were prepared; at the same time, comparative examples of 0.3 MPa (6% wall thickness) and 2.5 MPa (15% wall thickness) were prepared.

[0055] When other conditions in Example 1 remain unchanged, the data comparison is shown in Table 10 below: Table 10 Comparison results: When the microcapsule rupture threshold is 0.5-2.0 MPa, the conductivity recovery rate of the present invention is ≥88%, and the cycle life is ≥80,000 times; when the microcapsule rupture threshold is too low (such as 0.3 MPa) or too high (such as 2.5 MPa), the conductivity recovery rate is ≤75%.

[0056] Example 5: Methylamine lead bromide perovskite ( ) preparation and performance testing 1. Material preparation and testing methods 1.1 Photovoltaic layer preparation raw material: Methylamine ( )、Lead bromide( ), dimethyl sulfoxide (DMSO) solvent; Graphene quantum dots (GQDs, particle size 5-20 nm).

[0057] Process steps: (a) and It was dissolved in DMSO at a molar ratio of 1:3 and stirred at room temperature for 24 hours to form a precursor solution; (b) Spin coating deposition on PI substrate layer (rotation speed 3000 rpm, time 30 s) with thicknesses of 200 nm, 300 nm, 400 nm, and 500 nm; (c) Surface modification: spraying graphene quantum dots (concentration 0.1 mg / mL), coverage ≥ 95% (SEM verification).

[0058] 1.2 Performance Testing Light absorption efficiency: UV-Vis spectrophotometer (wavelength 300-800 nm); Carrier lifetime: time-resolved photoluminescence spectroscopy (TRPL); Bending stability: Conductivity test (four-probe method) after 100,000 bends with a curvature radius of 5 mm.

[0059] 2. Experimental results and data comparison 2.1 Light absorption and carrier lifetime Table 11: Data of light absorption and carrier lifetime at different thicknesses 2.2 The bending stability test data is shown in Table 12.

[0060] Table 12 3. Comparison results As shown in Table 12, when other conditions remain unchanged, The light absorption efficiency and carrier lifetime of the photovoltaic layer are significantly higher than those of the traditional solution (ITO electrode). Within the thickness range of 200 to 500nm, the light absorption efficiency is ≥81%, and the conductivity retention rate after bending is ≥82%. The optimal thickness is 300nm.

[0061] Example 6: Preparation and performance testing of double-layer AB stacked graphene conductive layer 1. Material preparation and testing methods 1.1 Preparation of graphene conductive layer CVD process parameters: Substrate: copper foil (99.8% purity, thickness 25 μm); Gas mixture ratio: methane ( ) volume concentration 5%, 10%, 15%, hydrogen ( )balance; Growth temperature: 1000℃, 1025℃, 1050℃; Growth time: 30 minutes.

[0062] Transfer process: PMMA-assisted wet transfer to the surface of the perovskite layer, and the interface was annealed (200°C, argon protection).

[0063] 1.2 Structural characterization and performance testing Interlayer structure: Transmission electron microscopy (TEM) analysis of interlayer spacing and stacking; Electrical properties: Four-probe method to measure square resistance, Hall effect test to test carrier mobility; Optical properties: UV-visible spectrophotometer to measure transmittance; Mechanical stability: change in square resistance after 100,000 bends (radius of curvature 5 mm).

[0064] 2. Experimental results and data comparison 2.1 Process parameter optimization is shown in Table 13.

[0065] Table 13: 2.2 Mechanical stability test is shown in Table 14 Table 14 3. Technical effect analysis 3.1 Advantages of double-layer AB stacking: Carrier mobility improvement: double-layer AB stacking ( ) is more than single layer ( ) increased by 48.6% due to the formation of additional transmission channels through π-π coupling between layers; Enhanced mechanical stability: The double-layer structure disperses stress through interlayer sliding, and the resistance increase after bending is only 7.5% (32% for a single layer).

[0066] 3.2 Process parameter verification: Methane concentration 5-15%: too low a concentration (such as 3%) results in discontinuous graphene, while too high a concentration (such as 20%) generates a multi-layer disordered structure; Temperature 1000-1050℃: When the temperature is lower than 950℃, the graphene domain size is less than 10 μm (carrier mobility is less than 3000 ).

[0067] Example 7: Preparation and performance testing of microcapsule repair agent 1. Material preparation and testing methods 1.1 Preparation of microcapsule repair agent Core material composition: polypyrrole (PPy) and polyaniline (PANI), with mass ratios of 3:1, 2:1, and 1:1, respectively; Wall material: polyurethane (PU), wall thickness is controlled at 10%, 12.5%, and 15% of the core material diameter; Process: Microcapsules were synthesized by emulsion polymerization, with a core diameter of 10 μm (verified by laser particle size analyzer); Adjust the emulsification speed (800-1200 rpm) and cross-linking time (2-6 hours) to control the distribution density at 500, 650, (SEM statistics).

[0068] 1.2 Performance Testing Rupture threshold: universal testing machine compression test (ASTM D5628); Conductivity recovery rate: The four-probe method measures the conductivity before and after repair ( ); Bending stability: Change in interface resistance after 100,000 bends (radius of curvature 5 mm) (GB / T 2423.34).

[0069] 2. Experimental results and data comparison 2.1 Mass ratio and repair performance data are shown in Table 15.

[0070] Table 15 2.2 The influence of wall thickness and distribution density is shown in Table 16.

[0071] Table 16 3. Technical effect analysis 3.1 Quality ratio optimization: The 2:1 mass ratio has the best comprehensive performance (conductivity recovery rate 92%, rupture threshold 2.0 MPa), because the conductivity of PPy and PANI is complementary; The conductivity recovery rates of the super-ratio contrast (4:1 or 1:2) were all ≤75%.

[0072] 3.2 Synergistic effect of wall thickness and distribution density: Wall thickness 10-15%: balance the rupture threshold and the release efficiency of the repair agent (≥90%); Distribution density : Too low density (<500) leads to uneven repair, while too high density (>800) affects flexibility (bending modulus>1.5 GPa).

[0073] Example 8: Plasma treatment process optimization and interface performance testing 1. Material preparation and processing technology 1.1 Substrate processing Substrate material: 50 μm thick polyimide (PI) film; Plasma equipment: radio frequency glow discharge system (frequency 13.56 MHz, oxygen / argon mixed gas ratio 1:1); Process parameters: Power density: , , (claim range endpoints and intermediate values); Processing time: fixed at 90 seconds; Gas flow rate: 20 sccm, chamber pressure 10 Pa.

[0074] 1.2 Perovskite layer deposition Spin coating deposition layer (thickness 300 nm), and an untreated substrate was used as a comparative example.

[0075] 2. Performance testing and data comparison 2.1 Surface characteristics analysis is shown in Table 17.

[0076] Table 17 2.2 Photoelectric and mechanical properties are shown in Table 18.

[0077] Table 18 3. Technical effect analysis 3.1 Oxygen content and interface binding energy: Power density When the oxygen element increases by 8.5-11.8 at%, the interface binding energy ≥ , significantly higher than the control group ( ); Out-of-range risk: power density Leading to surface carbonization, the interface bonding energy is reduced to , proving the technical necessity of the scope of the claims.

[0078] 3.2 Photoelectric performance optimization: Optimum power density When the surface roughness is reduced (4.8 nm) and the oxygen active sites are increased, the photoelectric conversion efficiency reaches 25.6%, which improves the adhesion of the perovskite layer. Power density and The efficiency is slightly lower, but still significantly better than the comparative example.

[0079] 3.3 Mechanical stability: Power density The resistance of the treated substrate increases by only 7% after bending due to the high interface bonding energy ( ), inhibiting crack propagation.

Claims

1. A flexible self-healing touch screen based on perovskite-graphene heterojunction, characterized in that: Includes the following components stacked in order: (a) Flexible transparent substrate made of polyimide (PI) or polyethylene terephthalate (PET), with a thickness of 10-50 μm and a plasma-treated surface; (b) a perovskite photovoltaic layer disposed on the substrate, wherein the material of the perovskite photovoltaic layer is formamidinium lead iodide perovskite ( ) or methylamine lead bromide perovskite ( ), with a thickness of 200-500 nm, and the surface is modified with graphene quantum dots to improve light absorption efficiency; (c) a graphene conductive layer covering the perovskite photovoltaic layer, which is directly grown by chemical vapor deposition (CVD) and has a square resistance of ≤50 Ω / sq and a transmittance of ≥90%, and forms a heterojunction structure with the perovskite layer; (d) a self-healing functional layer embedded in the graphene conductive layer, which is a thermoreversible polymer network containing dynamic covalent bonds or a conductive polymer repair agent encapsulated in microcapsules, wherein the dynamic covalent bonds are Diels-Alder bonds, the glass transition temperature of the thermoreversible polymer network is 60-80°C, and the microcapsule rupture threshold is 0.5-2.0 MPa; (e) An energy management module electrically connected to the graphene conductive layer, comprising an energy storage unit composed of a micro supercapacitor and a lithium-ion battery connected in parallel, and a power distribution chip integrating an adaptive algorithm, wherein the algorithm calculates the real-time power supply of the touch electrode by the following formula: ; in: : Real-time power supply of touch electrode, unit ; L: illuminance value collected by the ambient light sensor, ; F: Touch pressure sensor feedback value, ; : Operation mode reference power, defined as follows: ; , : Dynamic weight coefficient, satisfying , and updated every 30 seconds according to the following formula: ; α: power adjustment factor, value range [0.8,1.2].

2. The flexible self-repairing touch screen according to claim 1, characterized in that: The graphene conductive layer is a few-layer graphene film with a double-layer AB stacking structure, with an interlayer spacing of 0.34±0.02 nm, and the CVD method uses a methane / hydrogen mixed gas with a methane volume concentration of 5-15% and a growth temperature of 1000-1050°C.

3. The flexible self-repairing touch screen according to claim 1, characterized in that: In the conductive polymer repair agent wrapped in the microcapsule, the mass ratio of polypyrrole to polyaniline is 3:1 to 1:1, the wall thickness of the microcapsule is 10-15% of the core material diameter, and the spatial distribution density of the microcapsule in the graphene conductive layer is .

4. The flexible self-repairing touch screen according to claim 1, characterized in that: The plasma treatment adopts radio frequency glow discharge mode with a power density of The oxygen content of the treated substrate surface increases by 8-12 at%, and the interface binding energy with the perovskite layer is ≥ .

5. The flexible self-repairing touch screen according to claim 1, characterized in that: The weight coefficient update function further includes a resistance compensation term: ; in: : Initial square resistance of graphene conductive layer, unit: Ω / sq; : Real-time monitoring of square resistance, unit Ω / sq.

6. The flexible self-repairing touch screen according to claim 5, characterized in that: When Δω>0.8 is detected and lasts for more than 10 seconds, the emergency energy supply protocol is activated: ; in: τ=30 s: time constant; : Real-time output power of the perovskite layer, unit .

7. The flexible self-repairing touch screen according to claim 1, characterized in that: The cross-linking density of dynamic covalent bonds in the thermoreversible polymer network is to , and the repair efficiency satisfies: ; in: : The conductivity of the graphene conductive layer after self-healing treatment, unit S / m; : conductivity in the original undamaged state, unit: S / m; : The glass transition temperature of the thermoreversible polymer network defined in claim 1, in °C; T: Applied external heating temperature, unit: °C.

8. A mobile terminal device, characterized in that: It comprises the flexible self-repairing touch screen as described in any one of claims 1 to 7, and the energy management module is integrated with the terminal battery system through a reversible plug interface.

9. The mobile terminal device according to claim 8, characterized in that: The communication interface between the energy management module and the terminal mainboard adopts Protocol, data transmission rate ≥ 400 kbps, and has the following collaborative control logic: ; in: : The state of charge of the terminal battery, ranging from 0-100%; : The safe output power of the perovskite photovoltaic layer is calculated as follows: ; : Real-time output power of the perovskite layer, unit .

10. The mobile terminal device according to claim 9, characterized in that: The device housing is provided with a deformation sensor array linked to the self-healing functional layer, with a sensor spacing of ≤500 μm. When a bend with a curvature radius R<5 mm is detected, the following compensation mechanism is triggered: ; in: : Change in curvature radius, unit: mm; : The radius of curvature of the device in its initial planar state (defined as ).

Citation Information

Patent Citations

  • Light detector based on graphene and nano-structure perovskite material and manufacturing method

    CN104779352A

  • Perovskite photoactive composite layer, preparation method thereof, and perovskite solar cell comprising the same

    US20240414928A1

  • Organic Responsive User Interface System and Method of Use

    US20240427467A1